2010
DOI: 10.3109/01443615.2010.497873
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Clomiphene citrate or aromatase inhibitors combined with gonadotropins for superovulation in women undergoing intrauterine insemination: A prospective randomised trial

Abstract: The objective of this study was to test the use of letrozole in combination with follicle-stimulating hormone (FSH) vs clomiphene citrate (CC) with FSH for ovarian hyperstimulation prior to intrauterine insemination (IUI). A prospective randomised trial in which 280 women with unexplained infertility were randomised to 100 mg of CC (141 patients, 219 cycles) or 5 mg of letrozole daily (139 patients, 215 cycles) for 5 days starting on day 3 of menses both combined with gonadotropins for ovarian stimulation prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 30 publications
4
22
0
1
Order By: Relevance
“…4,12,13 Additional studies have also shown that letrozole does not increase the risk for congenital malformations with ovulation induction. 14 If our data are confirmed, this and future research may save some NOA patients from surgery. Future research in this field should also consider the possibility that letrozole administration could improve sperm yield in TESE/FNA and/or sperm retrieval for intracytoplasmic sperm injection.…”
Section: Discussionsupporting
confidence: 51%
“…4,12,13 Additional studies have also shown that letrozole does not increase the risk for congenital malformations with ovulation induction. 14 If our data are confirmed, this and future research may save some NOA patients from surgery. Future research in this field should also consider the possibility that letrozole administration could improve sperm yield in TESE/FNA and/or sperm retrieval for intracytoplasmic sperm injection.…”
Section: Discussionsupporting
confidence: 51%
“…The current study reported a clinical pregnancy rate of 25% and a live birth rate of 21.3% for the total letrozolestimulated cycles, regardless of the ovulation triggering protocol; the rates that accord with those formerly stated in various studies evaluated letrozole superovulation in women with UI (table 4) [11][12][13][14][15][16] . However, dual triggering by FSH/hCG compared to hCG alone improved the outcome of Letrozole-stimulated IUI cycles manifested as significantly higher pregnancy rate pre-cycle (12.5% vs. 5.8%: p=0.049) and per-woman (33.33% vs. 16.67%: p=0.049), and a significantly higher live birth rate (29.6% vs, 12.5%; p= 0.039).…”
Section: Discussion:-supporting
confidence: 66%
“…However, dual triggering by FSH/hCG compared to hCG alone improved the outcome of Letrozole-stimulated IUI cycles manifested as significantly higher pregnancy rate pre-cycle (12.5% vs. 5.8%: p=0.049) and per-woman (33.33% vs. 16.67%: p=0.049), and a significantly higher live birth rate (29.6% vs, 12.5%; p= 0.039). The reported pregnancy and live birth rates in the FSH/hCG trigger group are superior to those reported in diverse studies evaluating different letrozole-stimulated IUI protocols in women with UI (table 4) [11][12][13][14][15][16] . To our knowledge, this is the first trial planned to appraise the effect of FSH/hCG dual triggering in letrozole-stimulated cycles in ladies with UI.…”
Section: Discussion:-mentioning
confidence: 85%
“…However, in cycles involving adjunctive treatment with letrozole, serum E 2 concentrations have limited utility. Studies in infertile anovulatory women have demonstrated that letrozole can induce ovulation and is associated with lower peak E 2 levels than with other methods of ovulation induction [6,7]. Because E 2 levels rise only modestly during treatment with gonadotropins and letrozole, it might be assumed that risk for developing OHSS is low.…”
Section: Discussionmentioning
confidence: 99%